Towards Understanding Language: Two Important Philosophical Perspectives in History - Singh, Vibhav Pal (IISER Mohali, 2024)
In this thesis, I tried to study two very prominent thoughts in the Philosophy of Language and Linguistics. The nature of this thesis is exploratory. One of the Two traditions I studied, was Cartesian Philosophy, which although it gets its name from the very well-known figure in Philosophy, Rene Descartes, was in fact elaborated by many other scholars with and after him. Because Descartes himself did not do any work explicitly on the Philosophy of Language. In their theory, human mind and human language are intricately connected. Their theories about language were based on how mind works, and in turn from the structure of language they wanted to understand how mind works. The second tradition that I explored, were the Ideas of Ferdinand de Saussure. He was a Swiss Linguist. His ideas were published in a textbook, which was actually a compilation of his teachings in the University of Geneva, which came out in 1916. His ideas were radically different from Cartesian trend. He proposed the Social perspective of language. He proposed that language is a Social Phenomenon. Language is the social use of material facts. And his ideas eventually turned out to be quite impactful in Social Sciences, and turn into what we know as Structuralism.
Keywords: Language; Linguistic; Philosophy